THE FUNCTION OF STYLISTIC AND SYNTACTIC DEVICES IN THE CONSTRUCTION OF THE SYSTEM OF IMAGERY IN GEORGE GORDON BYRON’S POETIC WORKS - Toshpulatov , Bekhzod (Zamonaviy filologiya muammolari, 2025)
Abstract: This article analyzes the use, role, and artistic manifestation of stylistic and syntactic devices in the creation of imagery in the poetic works of George Gordon Byron, one of the prominent figures of English Romanticism. The study focuses on the harmony and expressive power of linguistic tools in revealing and interpreting the aesthetic essence of Byron’s imagery. As a result, Byron is recognized as a creative artist who, through his stylistic and syntactic choices, constructed a unique poetic world.